Procalcitonin and High APACHE (Acute Physiological and Chronic Health Evaluation) Level Are Associated with the Course of Acute Kidney Injury in Patients with SARS-CoV-2 - Jorge Andrade Sierra; Claudia Delgado Astorga; Miriam Gabriela Nava Vargas; Enrique Rojas Campos; Kevin Javier Arrelano Arteaga; Karla Hernández Morales; Carlos A. Andrade Castellanos; Antonio de Jesús Andrade-Ortega; Luis Gerardo González Correa (International Journal of Clinical Practice)
Background. Acute kidney injury (AKI) is associated with poor outcomes in patients infected with SARS-CoV-2. Sepsis, direct injury to kidney cells by the virus, and severe systemic inflammation are mechanisms implicated in its development. We investigated the association between inflammatory markers (C-reactive protein, procalcitonin, D-dimer, lactate dehydrogenase, and ferritin) in patients infected with SARS-CoV-2 and the development of AKI. Methods. A prospective cohort study performed at the Civil Hospital (Dr. Juan I. Menchaca) Guadalajara, Mexico, included patients aged >18 years with a diagnosis of SARS-CoV-2 pneumonia confirmed by RT-PCR and who did or did not present with AKI (KDIGO) while hospitalized. Biomarkers of inflammation were recorded, and kidney function was estimated using the CKD-EPI formula. Results. 291 patients were included (68% males; average age, 57 years). The incidence of AKI was 40.5% (118 patients); 21% developed stage 1 AKI, 6% developed stage 2 AKI, and 14% developed stage 3 AKI. The development of AKI was associated with higher phosphate (p=0.002) (RR 1.39, CI 95% 1.13–1.72), high procalcitonin levels at hospital admission (p=0.005) (RR 2.09, CI 95% 1.26–3.50), and high APACHE scores (p=0.011) (RR 2.0, CI 95% 1.17–3.40). The survival analysis free of AKI according to procalcitonin levels and APACHE scores demonstrated a lower survival in patients with procalcitonin >0.5 ng/ml (p=0.001) and APACHE >15 points (p=0.004). Conclusions. Phosphate, high procalcitonin levels, and APACHE levels >15 were predictors of AKI development in patients hospitalized with COVID-19.